Proposal Transisi Bisnis Perusahaan dalam Perspektif Teologis Pertemuan Ekonomi Fransiskus - Irianto, Eugenius Dwi Ardhika; Manafe, Henny Angri; Man, Stanis; Wutun, Maria Bernadethe Mawarni Gelu (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
This article aims to outline the proposal for corporate business transition submitted by participants of the Economy of Francesco meeting. Through a literature review method, the proposal from meeting participants is analyzed within the framework of the new economic model advocated by St. Francis and Pope Francis. The research findings indicate that participants emphasize the importance of redefining the mission and role of companies, adopting sustainable business models, leveraging technology for the common good, and establishing supportive institutions and ecosystems for the transition process. The transition of corporate businesses should be grounded in shared values and goals. This grounding requires companies to redefine the concept of values underlying every economic decision and the financial accounting system of the company.